Relationship between performance appraisal communication, procedural justice and job satisfaction - Azman Ismail,; Nur Asilah Kithuru Mohamed,; Mohamad Rahmad Rayee, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Performance appraisal communication is a segment of performance appraisal management denoting the process of sharing and transferring appraisal information from appraiser to appraisee either face-to-face or through technical and communication gadgets. The traditional performance appraisal was based on past performance of the employees, single-source feedback, non-participation style in decision making and boss-centred approach. It did not consider the development aspects of the employee performance as it was preoccupied with judging the performance of the organization as a whole. To address the drawback of this approach, modern approaches were introduced in the era of globalization which centred on humanistic perspectives, system thinking and contingency views. In the light of the new approaches, this paper examines the effect of performance appraisal communication and procedural justice on job satisfaction using 99 usable questionnaires collected from employees who work at public tertiary educational institutions in East Malaysia. The outcomes of stepwise regression analysis showed that relationship between feedback, treatment and procedural justice significantly correlated with job satisfaction. In sum, this result demonstrates that the ability of appraisers to appropriately provide feedback and treatment will strongly invoke appraisees’ feelings of procedural justice and this may lead to an enhanced job satisfaction in the organization studied.